Stabilization of Palladium Catalysts for the Heck Reaction by Support Functionalization and Solvent Selection. Issue 11 (26th September 2014) - Oliveira, Rafael L.; Hooijmans, Jasper B. F.; E. de Jongh, Petra; Klein Gebbink, Robertus J. M.; P. de Jong, Krijn
Abstract Pd nanoparticles were synthesized on nonfunctionalized and functionalized SBA‐15 grafted with thiol or amine groups. The resulting materials were used as catalysts to study the influence of these functional groups for a similar Pd particle size of approximately 2 nm on the Heck reaction that uses iodide substrates. The nonfunctionalized catalysts lost their activity quickly because of Pd leaching and particle growth. However, if a mixed solvent that consisted of toluene and DMF was used and thiol groups were grafted on SBA‐15, we were able to reduce the Pd leaching and particle growth to thus obtain a more stable catalyst in which an important role of the ligands was to recapture Pd. However, heterogeneity tests, such as a hot filtration test and poisoning experiments, gave a strong indication that Pd still leached from the support and that homogeneous Pd species were mainly responsible for the activity. Pd on S‐functionalized SBA‐15 was able to catalyze the Heck reaction using different substrates to achieve good activity and selectivity in most cases.